Safety and Tolerability of PCSK9 Inhibitors: Current Insights - Kosmas CE; Skavdis A; Sourlas A; Papakonstantinou EJ; Peña Genao E; Echavarria Uceta R; Guzman E (Dove Medical Press, 2020)
Constantine E Kosmas,1 Andreas Skavdis,2 Andreas Sourlas,3 Evangelia J Papakonstantinou,4 Edilberto Peña Genao,5 Rogers Echavarria Uceta,5 Eliscer Guzman1 1Division of Cardiology, Department of Medicine, Montefiore Medical Center, Bronx, NY, USA; 2School of Medicine, University of Athens, Athens, Greece; 3School of Medicine, University of Crete, Heraklion, Greece; 4General Directorate of Public Health and Social Welfare, Attica Region, Athens, Greece; 5Cardiology Clinic, Cardiology Unlimited, PC, New York, NY, USACorrespondence: Constantine E Kosmas 168-24 Powells Cove Blvd., Beechhurst, NY 11357, USATel +1-646-734-7969Email cekosmas1@gmail.comAbstract: The current era of preventive cardiology continues to emphasize on low-density lipoprotein cholesterol (LDL-C) reduction to alleviate the burden of atherosclerotic cardiovascular disease (ASCVD). In this regard, the pharmacological inhibition of proprotein convertase subtilisin/kexin type 9 (PCSK9) enzyme via monoclonal antibodies has emerged as a novel lipid-lowering therapy, leading to a marked reduction in circulating LDL-C levels and subsequent improvement of cardiovascular outcomes. As these agents are increasingly used in current clinical practice, mounting scientific and clinical evidence supports that PCSK9 inhibitors offer an excellent safety and tolerability profile with a low incidence of adverse events. Notably, the most frequently reported side effects are injection-site reactions. In contrast to statins, PCSK9 inhibitors do not appear to exert a detrimental effect on glycemic control or to increase the incidence of new-onset diabetes mellitus. Accumulating evidence also indicates that PCSK9 inhibitors are a safe, well-tolerated and effective therapeutic strategy for patients with statin intolerance. On the other hand, as PCSK9 inhibitors reduce LDL-C to unprecedented low levels, a large body of current research has examined the effects of their long-term administration on neurocognition and on levels of vitamin E and other fat-soluble vitamins, providing encouraging results. This review aims to present and discuss the current clinical and scientific evidence pertaining to the safety and tolerability of PCSK9 inhibitors.Keywords: hypercholesterolemia, cardiovascular disease, CVD, PCSK9 inhibitors, safety, tolerability